Decolonising the Conceptions of Race in South Africa: A Fanonian Analysis (The Strategic Review for Southern Africa, 2020)
This article claims that racism is undoubtedly the foundation upon which colonialism prospered and assumed its nature and characteristics. Hence, a rethinking of issues associated with conceptions of race is simultaneously a decolonisation process. It is impossible if not inconceivable to think of racism in post-apartheid South Africa without making reference to the colonial nature of the practice. It is beyond dispute that the issue of race and identity is still a bone of contention in post-apartheid South Africa. A lot has been written and done in this regard but this article argues that from what has been accomplished no effective and workable recommendations have been successfully put forward. The article challenges the prevailing recommendations and proposals to be revised beyond anger and emotion. Such an endeavour does not perceive anger and emotion as irrelevant but pushes to re-channel them in ways that support emancipatory strategies that serve to unlearn racial stereotypes. It proposes not a solution but a foundation of a thinking process - inspired by Fanon - which seeks to understand the problem before we attempt to propose a solution.
Keywords: colonialism; apartheid; post-apartheid; racism; decolonisation; emancipatory; Fanon